Kamo's escape - Pennac, Daniel; Ardizzone, Sarah (Walker London, 2004)
Kamo has a bad feeling about the old bike-like something bad will happen if he rides it. It turns out he's right and as he lies in a hospital bed talking in his sleep, it seems to his friends that Kamo is becoming someone else-someone fierce and strong; someone who can outstare a starving wolf and escape from anywhere ... Suggested level: intermediate, junior secondary